Neuron-Specific Glycine Metabolism Links Transfer RNA Epitranscriptomic Regulation to Complex Behaviors - Jennifer Blaze; Viviana Dolores Evans; Jessica Abigail Feria Pliego; Petr Unichenko; Behnam Javidfar; Soeren Heissel; Hanan Alwaseem; Zachary Pennington; Denise Cai; Henrik Molina; Christian Henneberger; Schahram Akbarian (Biological Psychiatry Global Open Science)
Background: The presence of treatment resistance in neuropsychiatric disease suggests that novel mechanism-based discoveries and therapies could benefit the field, with a viable candidate being transfer RNA (tRNA) epitranscriptomics. Nsun2 tRNA methyltransferase depletion in mature neurons elicits changes in complex behaviors relevant for fear, anxiety, and other neuropsychiatric phenotypes. However, it remains unclear whether this is due to dysregulated tRNAs or metabolic shifts that impact the neuronal translatome by activation of stress messengers together with alterations in amino acid supply. Methods: To link specific molecular alterations resulting from neuronal Nsun2 ablation to neuropsychiatric phenotypes, we used drug-induced phosphoactivation of stress response translation initiation factors together with disruption of NSUN2-regulated glycine tRNAs and cell type–specific ablation of the glycine cleavage system modeling the excessive upregulation of this amino acid in the Nsun2-deficient brain. Changes in extracellular glycine levels were monitored by an optical glycine Förster resonance energy transfer (FRET) sensor in the hippocampus, and behavioral phenotyping included cognition, anxiety-like behavior, and behavioral despair. Results: Increased motivated escape behaviors were specifically observed in mice with neuron-specific ablation of Gldc, resulting in an excess in cortical glycine levels comparable to a similar phenotype in mice after deletion of neuronal Nsun2. None of these phenotypes were observed in mice treated with tunicamycin for chemoactivation of integrative stress response pathways or in mice genetically engineered for decreased glycine tRNA gene dosage. In the Nsun2-deficient brain, dynamic glycine profiles in the hippocampal extracellular space were fully maintained at baseline and in the context of neuronal activity. Conclusions: Alterations in neuronal glycine metabolism, resulting from targeted ablation of the glycine cleavage system or disruption of the tRNA regulome, elicit changes in complex behaviors in mice relevant for neuropsychiatric phenotypes.